Perancangan dan Evaluasi User Experience Aplikasi Virtual Event Menggunakan User Experience Questionnaire - Kinanthi, Wikan Chandra; Setiyawati, Nina (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Since the end of 2019, the world has experienced a COVID-19 pandemic which affects every aspect of life. To get around and adapt in the new normal era, technology is the main tool that plays a role in changing human interaction behavior from offline to online. This encourages the diffusion of digital technology in society. One of them is the organization of events such as seminars and workshops that must continue to take place from the needs of the community. The platform commonly used in conducting virtual events is Zoom Meeting. However, there are several features that have not been accommodated in Zoom Meeting. In this study, user experience and user interface design for the EventGo visual event application were designed. Design on user experience on Zoom Meeting. Therefore, an evaluation of the UX of the Zoom Meeting application was carried out using UEQ. The UI/UX design of the EventGo application also uses UEQ. From the evaluation results, it was found that there was an increase in the average UX aspect of the EventGo application design.